1414. Substance Use Treatment Utilization Among Women with and at Risk for HIV. (15th December 2022) - Fujita, Ayako W; Ramakrishnan, Aditi; Mehta, Cyra Christina; Yusuf, Oyindamola; Wilson, Tracey; Shoptaw, Steven; Carrico, Adam; Adimora, Adaora A; Eaton, Ellen; Cohen, Mardge; Cohen, Jennifer; Adedimeji, Adebola; et al.
Abstract: Background: Substance use (SU) contributes to poor health outcomes, yet limited data exist to inform strategies to optimize SU treatment among people with HIV (PWH). We describe SU and SU treatment utilization among women with and at risk for HIV in the Women's Interagency HIV Study (WIHS). Methods: We included data from participants enrolled in 10 WIHS sites from 2013-2020. Current SU was defined as self-reported, non-medical use of drugs in the past year, excluding use of only marijuana. SU treatment utilization was determined by self-reported use of a drug treatment program in the past year. Multivariable regression models were used to determine associations between participant characteristics and SU treatment. Results: Among 2559 women (1802 HIV+, 757 HIV-), 66% (n= 1690) reported lifetime SU (65% HIV+, 69% HIV-), and 14% (n=367) reported current SU (13% HIV+, 18% HIV-). Among women with current SU, 71% reported crack/cocaine, 40% opioids, 12% any intravenous drug, 6.5% tranquilizers, and 6.5% methamphetamines. Of these women, 77% reported smoking cigarettes, 52% marijuana use, and 27% using >7 drinks/week. Among women with current SU, 42% (n=155) reported any treatment in the past year (40% HIV+, 45% HIV-); the most common treatments were methadone (64%), narcotics anonymous (29%), inpatient (28%), and outpatient programs (16%). Among women with opioid use (n= 147), 67% reported methadone use in the past year compared to only 5% using buprenorphine/naloxone. In multivariable analysis, HIV seropositivity and concurrent alcohol or marijuana use were associated with lower odds of SU treatment, and visit with a psychiatrist/counselor with higher odds of treatment (Table). In a separate model including only women with HIV, SU treatment was not associated with having an HIV care visit or viral suppression. Table- part 1 Table - part 2 Conclusion: In the WIHS cohort, SU treatment utilization was higher than expected, especially for methadone use, reflecting the resilience of a population which is known to face stigma and barriers to treatment. Still, our analysis highlights opportunities for accessing SU treatment in the context of HIV care for women with HIV, such as the need to prioritize providing buprenorphine/naloxone in HIV care settings. Disclosures: Steven Shoptaw, PhD, Alkermes Inc: Grant/Research Support|Gilead Sciences, Inc: Grant/Research Support Adaora A. Adimora, MD, MPH, Gilead: Advisor/Consultant|Gilead: Grant/Research Support|Merck: Advisor/Consultant|Merck: Grant/Research Support Ellen Eaton, MD, MPH, Gilead HIV Research Scholar: Grant/Research Support|Gilead HIV research scholar: Grant/Research Support.